Waqf of Raw Paddy Fields: A Model to Boost Sustainable Agricultural Land Protection in Indonesia’s Central Java Province (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
The high conversion of paddy fields in Central Java as Indonesia's most extensive rice production center is a crucial issue affecting future food security. This paper aims to design a waqf model for paddy fields integrated with the Rice Market Center (RMC) to maintain the integrity and sustainability of agricultural land and increase farmers' welfare. This study utilizes a qualitative method with a library research approach by adopting qualitative content analysis, which is strengthened by collecting primary data through in-depth interviews with experts of regulators, practitioners, and academics in the field of waqf and agriculture. The results indicate that the model of waqf management of paddy fields can be implemented through collaboration between nazhir and anchor companies (AC) in the form of regionally owned enterprises or agricultural SMEs. AC will act as an off-taker from the farmers' cooperative, then sell their processed products to RMC distribution channels such as state civil apparatus, modern markets, or Islamic boarding schools. This integration model is expected to be an alternative in increasing the welfare of farmers as well as food security in Central Java province.